2009
DOI: 10.1088/0957-4484/20/23/235702
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable shape-memory nanocomposite with excellent magnetism sensitivity

Abstract: This paper reports a kind of biodegradable nanocomposite which can show an excellent shape-memory property in hot water or in an alternating magnetic field with f = 20 kH and H = 6.8 kA m(-1). The nanocomposite is composed of crosslinked poly(epsilon-caprolactone) (c-PCL) and Fe(3)O(4) nanoparticles. The crosslinking reaction in PCL with linear molecular structure was realized using benzoyl peroxide (BPO) as an initiator. The biocompatible Fe(3)O(4) magnetite nanoparticles with an average size of 10 nm were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 32 publications
1
84
0
Order By: Relevance
“…the OM‐based resonance test was used for characterizing the elastic modulus of NWs in an accurate manner. In this method, the vibration spectra of a NW cantilever were obtained using optical interferometry, and the elastic modulus of NWs can thus be derived from the Euler–Bernoulli beam theory 151, 152, 153, 154. Detail information on this method will be introduced in Section 2.5.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
See 1 more Smart Citation
“…the OM‐based resonance test was used for characterizing the elastic modulus of NWs in an accurate manner. In this method, the vibration spectra of a NW cantilever were obtained using optical interferometry, and the elastic modulus of NWs can thus be derived from the Euler–Bernoulli beam theory 151, 152, 153, 154. Detail information on this method will be introduced in Section 2.5.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…The eigenmodes and corresponding quality factors of a vibrational object can then be precisely determined. SLDV techniques have recently been used to measure the vibration of nanostructures with diameters smaller than 50 nm 3, 151, 152, 153, 154. The high resolution of SLDV techniques allows for a simple experimental setup.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…Methods (i) and (ii) do not allow an adequate control of particle size and the variety of nanocomposites that can be prepared is considerably limited; using method (iii), which is the most versatile, particles can agglomerate easily when mixing with the matrix unless their surface is modified. Nanocomposites of magnetite or maghemite with a wide range of different thermoplastic polymers, from conventional polymers such as polypropylene [35], polystyrene [36][37][38], or poly(methyl methacrylate) [39], to biodegradable polymers [40,41] or even conducting polymers [42] have been prepared this way.…”
Section: Introductionmentioning
confidence: 99%
“…So this method can be useful if shape memory polymer cannot be actuated by direct heating methods. However, Zhou et al reported that for cross-linked poly(ε-caprolactone) polymers, magnetite composite shows better reactivity to hot water than alternating magnetic field [55].…”
mentioning
confidence: 99%